Apreciación del manejo ambiental y gestión de residuos sólidos de trabajadores de la agroindustria del cacao en Tamshiyacu. Loreto, 2024 - Pezo Pinedo, Claudio Jeanpier (2025)
This study has a quantitative approach, with a descriptive, correlational and transversal design, and aims to evaluate the environmental perception of management practices and characterize the solid waste generated in the company Tamshi SAC, located in Tamshiyacu, Loreto. The research was carried out with a sample made up of 12 managers and directors of the company. For data collection, structured surveys were applied, whose reliability was determined by Cronbach's alpha coefficient (0.774). The normality of the data was evaluated by the Shapiro-Wilk test, which justified the use of the Pearson correlation coefficient (R) for the analysis of relationships between variables. The results showed a high diversity in the types of solid waste generated, which underlines the need to design specific strategies for its management and valorization, in line with the objective of classifying and quantifying waste in the agro-industrial sector. Furthermore, although established management practices were identified, heterogeneity was observed in their application, which highlights the need to standardize procedures and optimize internal protocols. The staff's perception regarding the environmental impact of solid waste management, particularly in relation to water and soil contamination, reinforces the urgency of implementing corrective measures and mitigation strategies. In addition, a significant correlation was found between the adoption of better waste management practices and a more favorable perception of environmental management, which emphasizes the importance of optimizing these processes in the cocoa agroindustry to minimize its environmental impact and strengthen its sustainability.